Exercise tolerance during muscle contractions below and above the critical torque in different muscle groups - Abdalla, Leonardo Henrique Perinotto [UNESP]; Denadai, Benedito Sérgio [UNESP]; Bassan, Natália Menezes [UNESP]; Greco, Camila Coelho [UNESP] (My University, 2018)
The objective of this study was to test the hypotheses that end-test torque (ET) (expressed as % maximal voluntary contraction; MVC) is higher for plantar flexors (PF) than knee extensors (KE) muscles, whereas impulse above ET (IET) is higher for KE than PF. Thus, we expected that exercise tolerance would be longer for KE than PF only during the exercise performed above ET. After the determination of MVC, 40 men performed two 5-min all-out tests to determine ET and IET. Eleven participants performed a further 4 intermittent isometric tests, to exhaustion, at ET + 5% and ET-5%, and 1 test for KE at the exercise intensity (%MVC) corresponding to ET + 5% of PF. The IET (7243.2 ± 1942.9 vs. 3357.4 ± 1132.3 N·m·s) and ET (84.4 ± 24.8 vs. 73.9 ± 19.5 N·m) were significantly lower in PF compared with KE. The exercise tolerance was significantly longer for PF (300.7 ± 156.7 s) than KE (156.7 ± 104.3 s) at similar %MVC (~60%), and significantly shorter for PF (300.7 ± 156.7 s) than KE (697.0 ± 243.7 s) at ET + 5% condition. However, no significant difference was observed for ET-5% condition (KE = 1030.2 ± 495.4 s vs. PF = 1028.3 ± 514.4 s). Thus, the limit of tolerance during submaximal isometric contractions is influenced by absolute MVC only during exercise performed above ET, which seems to be explained by differences on both ET (expressed as %MVC) and IET values.
Keywords: Exercise; Exercise intensity domain; Fatigue; Isometric; Maximal voluntary contraction; Muscle volume